Miniaturized Circularly Polarized Doppler Radar for Human Vital Sign Detection - He, Yuchu; Gu, Changzhan; Ma, Haijiang; Zhu, Jiang; Eleftheriades, George V. (IEEE transactions on antennas and propagation, 2019)
In this paper, a miniaturized circularly polarized (CP) continuous wave Doppler radar system operating at 2.4 GHz is presented. The radar front end consists of one left-handed CP (LHCP) antenna and one right-handed CP (RHCP) antenna, which share a single patch antenna aperture. Orthogonal polarization is achieved through a modified ring-shaped quadrature hybrid coupler (QHC), and the resulting isolation between the two CP antennas is better than 30 dB. With 0 dBm input power to the transmitting antenna, the proposed radar system can accurately detect heartbeat and respiration movements of human test subjects under 1 m and over a wide angular range. The single dual CP antenna achieves 280% size reduction compared to a traditional two linear polarization patch antenna array with the same isolation level.